Quality of life and BMI changes in youth participating in an integrated pediatric obesity treatment program - Pratt, Keeley J; Lazorick, Suzanne; Lamson, Angela L; Ivanescu, Andrada; Collier, David N. (My University, 2013)
Changes in Quality of Life (QOL) measures over time with treatment of obesity have not previously been described for youth. We describe the changes from baseline through two follow up visits in youth QOL (assessed by the Pediatric Quality Life Inventory, PedsQL4.0), teen depression (assessed by the Patient Health Questionnaire, PHQ9A), Body Mass Index (BMI) and BMI z-score. We also report caregiver proxy ratings of youth QOL. A sample of 267 pairs of youth and caregiver participants were recruited at their first visit to an outpatient weight-treatment clinic that provides care integrated between a physician, dietician, and mental health provider; of the 267, 113 attended a visit two (V2) follow-up appointment, and 48 attended visit three (V3). We investigated multiple factors longitudinally experienced by youth who are overweight and their caregivers across up to three different integrated care visits. We determined relationships at baseline in QOL, PHQ9A, and BMI z-score, as well as changes in variables over time using linear mixed models with time as a covariate. Overall across three visits the results indicate that youth had slight declines in relative BMI, significant increases in their QOL and improvements in depression. We encourage clinicians and researchers to track youth longitudinally throughout treatment to investigate not only youth's BMI changes, but also psychosocial changes including QOL.
Keywords: Pediatric obesity, Quality of life, Depression, Obesity treatment